2020
DOI: 10.1021/acs.jpcb.0c04058
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Structure and Transport Properties of the Deep Eutectic Solvent Ethaline

Abstract: A range of techniques including physical property measurements, neutron scattering experiments, ab initio molecular dynamics, and classical molecular dynamics simulations are used to probe the structural, thermodynamic, and transport properties of a deep eutectic solvent comprised of a 1:2 molar ratio of choline chloride and ethylene glycol. This mixture, known as Ethaline, has many desirable properties for use in a range of applications, and therefore, understanding its liquid structure and transport properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 80 publications
9
113
0
Order By: Relevance
“…There are some noted deviations between simulations and experiments, seen as a shoulder at 1 Å −1 and peak splitting between 2 and 4 Å −1 in simulated 33 mol%. This is attributed to Ch–Ch interactions and is due to the mixed deuteration state of the experimental choline, something that was seen in Ethaline structure factors of a previous work 34 . A key advantage of the simulated structure factors is the ability to decompose the total profile and isolate individual molecule–molecule and atom–atom interactions.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…There are some noted deviations between simulations and experiments, seen as a shoulder at 1 Å −1 and peak splitting between 2 and 4 Å −1 in simulated 33 mol%. This is attributed to Ch–Ch interactions and is due to the mixed deuteration state of the experimental choline, something that was seen in Ethaline structure factors of a previous work 34 . A key advantage of the simulated structure factors is the ability to decompose the total profile and isolate individual molecule–molecule and atom–atom interactions.…”
Section: Resultsmentioning
confidence: 52%
“…It has been reported that the DES Ethaline has a higher viscosity than the corresponding pure HBD, EG 46 , 47 , an opposite trend seen in Glyceline. In a recent study by Zhang et al 34 , it was found that the hydrogen bonds between Cl and EG are much stronger than those between EG molecules and it was believed that these stronger Cl–EG interactions cause the increase in viscosity upon the addition of ChCl to EG. This is supported by 1 H NMR data in Figure S13 as discussed earlier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AIMD can also be applied to validate FFs for classical MD simulations [ 161 ]. For example, Jeong et al [ 141 ] utilized AIMD to develop atomistic polarizable FF for reline.…”
Section: Simulation Methods For Dessmentioning
confidence: 99%
“…Most of the works on the structures of classical DESs are based on ChCl, such as reline [ 64 , 70 , 76 , 123 , 208 , 209 , 210 , 211 , 212 ] (HBD is urea), ethaline [ 161 , 210 , 213 , 214 ] (HBD is ethylene glycol), glyceline [ 82 , 210 , 215 ] (HBD is glycerol), and propoline [ 216 , 217 ] (HBD is propylene glycol). Over the last five years, their structures and properties have been investigated intensively and the main interactions have been determined.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%